Pengaruh Profesionalisme, Etika Profesi, dan Locus of Control terhadap Kinerja Auditor (Studi pada Auditor KAP di Jakarta Selatan) - Aditya, Muhamad Reza; Taufan , Januar (Riviera Publishing, 2025)
This study aims to examine the influence of professionalism, professional ethics, and locus of control on auditor performance at Public Accounting Firms (KAP) in South Jakarta. This research employs a quantitative associative approach using primary data collected through questionnaires. The theoretical foundation used is attribution theory, which explains how individuals attribute behavior and performance based on internal and external factors. A total of 100 auditors were selected using simple random sampling. The data were analyzed using multiple linear regression and classical assumption tests. Simulated results show that professionalism and locus of control significantly influence auditor performance, while professional ethics does not have a significant effect. The implication of these findings is the need for enhanced professional training and development of auditors' internal locus of control to improve audit performance quality.